Disposable Carbon Dots Modified Screen Printed Carbon Electrode Electrochemical Sensor Strip for Selective Detection of Ferric Ions - Shao, Chien Tan; Suh, Cem Pang; Suk, Fun Chin (Hindawi Publishing Corporation, 2017)
A disposable electrochemical sensor strip based on carbon nanodots (C-Dots) modified screen printed carbon electrode (SPCE) was fabricated for selective detection of ferric ions (Fe3+) in aqueous solution. C-Dots of mean diameters within the range of 1–7 nm were synthesized electrochemically fromspent battery carbon rods.The analytical performance of this electrochemical sensor strip was characterized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS).The deposition ofC-Dots had enhanced the electron-transfer kinetics and current intensity of the SPCE remarkably by 734% as compared to that of unmodified SPCE. Under optimized conditions, the electrochemical sensor strip exhibited a linear detection range of 0.5 to 25.0 ppmFe3+ with a limit of detection (LOD) of 0.44 ± 0.04 ppm (at